Evolution and research trends in virtual reality and augmented reality technologies for the architecture, engineering, and construction (AEC) industry: a systematic review and science mapping approach - Sornoza-Parrales, Diego; Baque Vera, Günther Oberdam; Parrales Poveda, María Leonor; Macías-Parrales, Tania Maricela (Frontiers in Virtual Reality, 2025)
This systematic review and bibliometric analysis examine the evolution and research trends of Virtual Reality (VR) and Augmented Reality (AR) technologies within the Architecture, Engineering, and Construction (AEC) industry to identify key research themes, application domains, and future directions. A comprehensive literature search was conducted using both Scopus and Web of Science databases covering publications from 2015 to 2025 to ensure robust multi-database validation. After applying engineering subject area filters, the Scopus search yielded 1,301 articles while Web of Science returned 898 articles. The methodology combined quantitative bibliometric analysis using Bibliometrix software with qualitative thematic analysis of the most-cited and relevant studies following PRISMA guidelines. Performance analysis, science mapping, and co-occurrence analysis were employed to identify research clusters and trends across both databases. Cross-database validation confirmed convergent patterns in publication growth, thematic structure, and collaboration networks, with both databases demonstrating exponential growth and similar dominant research themes centered on digital twins, virtual reality applications, and BIM integration. This study provides a comprehensive quantitative mapping of VR/AR research in the AEC industry with multi-database validation, revealing the intellectual structure and research fronts. The integrated approach combining bibliometric analysis with thematic synthesis offers insights for researchers and practitioners to understand current applications, identify research gaps, and guide future technology adoption strategies.